Post a New Question

math-calculus

posted by .

4x+3/2x-1-2 = 6x+2/2x-1

(4x+3)(-2) = (6x+2)
-8x-6 = 6x+2
-14x-6 = 2
-14x = 8
x = 4/-7

i not think i did this right.

  • math-calculus -

    do you mean

    [ (4x+3)/(2x-1) ] - 2 = (6x+2)/(2x-1)

    ??????
    If so please use parentheses so I can tell numerator from denominator.
    If my guess is correct:
    (4x+3) -2 (2x-1) = 6x+2

    4x + 3 -4x + 2 = 6 x + 2
    3 = 6 x
    x = 1/2

  • math-calculus -

    sorry yes you are right but don't all 2x-1's cancel?

  • math-calculus -

    i think it supposed to be this
    (4x+3)(-2) = (6x+2)

  • math-calculus -

    [ (4x+3)/(2x-1) ] - 2 = (6x+2)/(2x-1)

    Multiply everything, all terms both sides including -2, by (2x-1)

    [(4x+3)/(2x-1)](2x-1)-2(2x-1) = [(6x+2)/(2x-1) ] (2x-1)

    You have to multiply that -2 by (2x-1) so the (2x-1) does not go away from the numerator when you clear it from the denominators.

    so
    (4x+3) -2 (2x-1) = 6x + 2

  • math-calculus -

    Perhaps your original line should read

    [(4x+3)/(2x-1)](-2) = (6x+2)/(2x-1)

    if so then

    -2(4x+3) = 6x+2

    -8x - 6 = 6x + 2

    -14 x = 8

    x = -4/7
    and your answer would be right

  • math-calculus -

    thank you but in back of book it say no solution so i very confused.

  • math-calculus -

    If my solution of x = 1/2 is correct (and I think it is'
    Then indeed the answer is NO SOLUTION
    because
    2x-1 = 0 if x = 1/2

    division by 0

  • math-calculus -

    I did not notice that, should have.

  • math-calculus -

    thank you so much i not notice that either. thanks :)

Answer This Question

First Name
School Subject
Your Answer

Related Questions

More Related Questions

Post a New Question